Recombinase polymerase amplification combined with CRISPR/Cas12a technology for rapid on-site detection of duck adenovirus 3 - Liang, Qi-Zhang; Chen, Wei; Bi, Yuhai; Wang, Weiwei; Liu, Rong-Chang; Fu, Qiu-Ling; Fu, Guang-Hua; Cheng, Long-Fei; Jiang, Nan-Song; Zhu, Ting; Chen, Hong-Mei; Huang, Yu (Frontiers in Microbiology, 2025)
Duck adenovirus 3 (DAdV-3) causes liver damage and bleeding, with morbidity rates ranging from 40 to 55% and mortality rates between 35 and 43%. Co-infection with other pathogens complicates disease control, significantly impacting the duck breeding industry. Currently, there have been no effective vaccines or treatments for DAdV-3. Therefore, rapid, specific, and sensitive detection methods are crucial for preventing and controlling this virus. Our study developed a lateral flow strip (LFS) detection method using recombinase polymerase amplification (RPA) and CRISPR/Cas12a. The RPA-CRISPR/Cas12a-LFS method, performed at 37°C, allowed for result visualization without sophisticated equipment. It targeted the DAdV-3 Fiber-2 gene and achieved a detection limit of 3.0 gene copies. Additionally, this method demonstrated high specificity, with no cross-reactivity to eight other avian viruses. The reaction time of RPA-CRISPR/Cas12a-LFS is only 45 min. Analysis of 95 waterfowl samples showed 98.95% consistency and agreement with quantitative polymerase chain reaction using the Fiber-2 RPA-CRISPR/Cas12a-LFS method. These findings highlighted the potential of this user-friendly, rapid, sensitive, and accurate detection method for on-site DAdV-3 detection.